ACADEMIC SELF CONCEPT AND ESTEEM SUPPORT IN MATHEMATICS STUDENTS: DO THEY AFFECT ACADEMIC BUOYANCY - ULFAH, KHOIRIYA; SUPRIANDI, AHMAD; SETIAWAN, NUGROHO ARIEF (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Mathematics is a discipline that is taught at all levels of education, including in higher education. However, mathematics in higher education is very different from mathematics at other levels. Learning mathematics in college requires higher-level cognitive abilities, such as analysis, synthesis, and evaluation. Students are required to achieve great achievements. The different learning system requires students to adapt and complete academic tasks and challenges. This can cause students to experience difficulties and fear of failure in meeting these tasks and challenges. This study aims to identify the relationship between academic self concept and esteem support with academic buoyancy in mathematics education students. The research method used is a quantitative approach. The subjects of this study were 103 mathematics education students. The data collection technique in this study used purposive sampling technique. Data collection tools in the form of a perception scale questionnaire regarding academic buoyancy scale (42 items), academic self concept scale (31 items), and esteem support scale (20 items). Data analysis in this study used multiple linear regression analysis. The results of this study indicate that there is a significant positive relationship between academic self concept and academic buoyancy with a correlation coefficient (R) of 0.593 with a significance of 0.001 (p<0.001). Meanwhile, the relationship between esteem support to academic buoyancy has a significant positive relationship with a correlation coefficient (R) of 0.909 with a significance of 0.001 (p <0.001). The effective contribution of the academic self-concept variable to the academic buoyancy variable is 19.6%. Meanwhile, the effective contribution provided by esteem support to the academic buoyancy variable is 72.6%. So it can be concluded that the higher the academic self concept, the higher the academic buoyancy. Meanwhile, the higher the esteem support, the higher the academic buoyancy. ABSTRAKMatematika merupakan suatu disiplin ilmu yang diajarkan di semua tingkat pendidikan, termasuk di perguruan tinggi. Namun, matematika di perguruan tinggi sangat berbeda dari matematika di jenjang lainnya. Pembelajaran matematika di perguruan tinggi memerlukan kemampuan kognitif tingkat tinggi, seperti analisis, sintesis, dan evaluasi. Mahasiswa diharuskan untuk meraih prestasi yang gemilang. Sistem pembelajaran yang berbeda menuntut mahasiswa untuk beradaptasi dan menyelesaikan tugas serta tantangan akademik. Hal ini dapat menyebabkan mahasiswa mengalami kesulitan dan ketakutan akan kegagalan dalam memenuhi tugas dan tantangan tersebut. Penelitian ini bertujuan untuk mengidentifikasi hubungan antara academic self concept dan esteem support dengan academic buoyancy pada mahasiswa pendidikan matematika. Metode penelitian yang digunakan pendekatan kuantitatif. Subjek penelitian ini yaitu mahasiswa pendidikan matematika sebanyak 103 subjek. Teknik pengumpulan data dalam penelitian ini menggunakan teknik purposive sampling. Alat pengumpulan data berupa kuisioner skala persepsi mengenai academic buoyancy scale (42 item), skala academic self concept scale (31 item), dan skala esteem support (20 item). Analisis data pada penelitian ini menggunakan analisis regresi linier berganda. Hasil penelitian ini menunjukkan bahwa terdapat hubungan positif yang signifikan antara academic self concept terhadap academic buoyancy dengan nilai koefisien korelasi (R) sebesar 0,593 dengan signifikansi sebesar 0,001 (p<0.001). Sedangkan untuk hubungan antara esteem support terhadap academic buoyancy memiliki hubungan positif signifikan dengan nilai koefisien korelasi (R) sebesar 0,909 dengan signifikansi sebesar 0,001 (p<0.001). Sumbangan efektif dari variabel academic self concept terhadap variabel academic buoyancy sebesar 19,6%. Sedangkan, sumbangan efektif yang diberikan oleh esteem support terhadap variabel academic buoyancy sebesar 72,6%. Maka dapat disimpulkan bahwa semakin tinggi academic self concept maka akan semakin tinggi academic buoyancy. Sedangkan, semakin tinggi esteem support maka akan semakin tinggi academic buoyancy.